PENGARUH CONTENT VISUAL AKUN TIKTOK @JAKARTA_TOURISM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN NUSANTARA KE DKI JAKARTA (Survei Terhadap Followers Tiktok @Jakarta_Tourism - Fadhil Ferdiansyah, (2020)
This research discusses the development of technology in delivering communication in the form of information that is packaged into a short-form video content through social media. The purpose of this study was to determine the magnitude of the influence of the TikTok @Jakarta_tourism account's visual content on the decision to visit Nusantara tourists to DKI Jakarta. The relevant theory in this study is the A-T-R (Awareness, Trial, Reinforcement) theory. This research was conducted using a quantitative approach with a survey method. The population of this study is the followers of the TikTok @Jakarta_tourism account, which amounted to 3932 followers, with a sample of 98 respondents who had been calculated using the Slovin technique with an error rate of 10%. The results of this study indicate that the correlation between the variable visual effect of the TikTok @Jakarta_tourism account and the variable of the decision to visit the Nusantara tourists to DKI Jakarta is 0.839 which means that the value has a very strong relationship because it is located between 0.800 - 0.1000, these results are determined based on the table Guidelines for interpreting the correlation coefficient. The magnitude of the contribution of variable X to the variable Y is measured by the coefficient of determination test that yields a result of 83.9%, this result is determined based on the R Square value obtained through the SPSS calculation. Then the calculation of the hypothesis with the t test formula, obtained t count of 15.108 which is determined at the 10% significance level. Thus the calculation of the variable influence the visual content of the TikTok @Jakarta_tourism (X) account with the decision variable of the Nusantara tourist's visit to DKI Jakarta (Y), it can be concluded based on the results of the hypothesis that Ho is rejected and Ha is accepted, which means there is a significant influence between the visual content of the TikTok @ account Jakarta_tourism on the decision to visit Nusantara tourists to DKI Jakarta.Keywords: Visual Content, TikTok @Jakarta_tourism, decision to visit, archipelago tourists, DKI Jakarta